To the Operating Room! Positive Effects of a Healthcare Clown Intervention on Children Undergoing Surgery - Gabriela Markova; Lukas Houdek; Zuzana Kocabova (Frontiers Media S.A., 2021)
In the present study we examined the positive effects of a healthcare clown intervention on children undergoing surgeries, and the role parent-child relationships may play in their effectiveness. Children between 5 and 12 years, who were scheduled to undergo elective surgical procedures in a large university hospital, were randomly assigned to an intervention group (IG; n = 35) that was visited by a healthcare clown, and a control group (CG; n = 27) that received treatment as usual (i.e., company of parents before the surgery). Children in both groups were videotaped and the videos were later used to rate their activity, arousal, emotional expressivity, and vocalizations. Additionally, children and parents rated their mood and perceived quality of life at several points during the procedure, and parents reported their perceptions of the relationship with their children. Results showed that children in the IG showed more positive emotions and vocalizations than children in the CG. Parents of children in the IG also reported more positive mood than parents of children in the CG. In contrast, children in the CG reported higher quality of life than children in the IG. Importantly, analyses showed considerable effects of the parent-child relationship on all outcome measures. Results of the present study demonstrate that a healthcare clown intervention had some positive effects on behaviors and mood of hospitalized children and their parents. Importantly, our findings also suggest that we need to consider the pre-existing "relationship microcosmos" that the clowns enter when assessing their effectiveness in the hospital.